Attention to local and global levels of hierarchical Navon figures affects rapid scene categorization - Brand, John; Johnson, Aaron P. (Frontiers in Psychology, 2014)
In four experiments, we investigated how attention to local and global levels of hierarchical Navon figures affected the selection of diagnostic spatial scale information used in scene categorization. We explored this issue by asking observers to classify hybrid images (i.e., images that contain low spatial frequency content of one image, and high spatial frequency content from a second image) immediately following global and local Navon tasks. Hybrid images can be classified according to either their low, or high spatial frequency content; thus, making them ideal for investigating diagnostic spatial scale preference. Although observers were sensitive to both spatial scales (Experiment 1), they overwhelmingly preferred to classify hybrids based on low spatial frequency content (Experiment 2). In Experiment 3, we demonstrated that low spatial frequency based hybrid categorization was faster following global Navon tasks, suggesting that low spatial frequency processing associated with global Navon tasks primed the selection of low spatial frequencies in hybrid images. In Experiment 4, replicating Experiment 3 but suppressing the low spatial frequency information in Navon letters by contrast balancing the stimuli examined this hypothesis. Similar to Experiment 3, observers preferred to classify hybrids based on low spatial frequency content; however and in contrast, low spatial frequency based hybrid categorization was slower following global than local Navon tasks.